STUDYING RELIGIOUS PLURALISM WITH HUMANITARIAN AND DEMOCRATIC PERSPECTIVES KH. HASYIM MUZADI - Halid, Ahmad; Siddiq al-Ghafir, Abu Aman; Marsidi, Yoyok (Kopertais Wilayah X Jawa Tengah, 2024)
As Islam grew in Indonesia, various religious ideas entered society, such as Wahhabism and Salafism from the Arabian peninsula. However, Indonesian society is not easily penetrated and influenced by these two ideologies. It has been proven that this understanding took tens or even hundreds of years to be absorbed by Indonesian society. And now these two ideologies have appeared to grip parts of the Indonesian nation and destroy the religious peace that has existed for hundreds of years in Indonesia. However, it is true what Media Indonesia wrote in its editorial that the Indonesian people can still have high hopes for the two true guardians of pluralism in Indonesia, namely NU and Muhammadiyah. After all, the Republic of Indonesia is a fixed price and pluralism is its guarantee. A unified state with Islam, Christianity, Catholicism, Hinduism and Buddhism will not be realized without there being tolerance between religious communities. There will be no peace and tranquility in carrying out worship when the values of